Electrocatalytic phenol degradation by a novel nanostructured carbon fiber brush cathode coated with graphene ink. (20th December 2017) - Mousset, Emmanuel; Wang, Zuxin; Hammaker, Joshua; Lefebvre, Olivier
Abstract: A new promising electrochemically-exfoliated graphene-based cathode for the electrocatalytic Fenton process was elaborated by an ink-coating technique. For this purpose, a method to coat graphene ink over a carbon-fiber brush substrate (referred to as Gr-Brush) was optimized and a 1:3 (w/w) Nafion ® :graphene ratio increased the H2 O2 accumulation yield by 40% (4.23 mg-H2 O2 L −1 cm −2 ), as compared to an uncoated brush. Such improvement was attributed to the higher electroactive surface area and conductivity of Gr-Brush, a fact confirmed by cyclic voltammetry and impedance measurements. Due to a remarkable raise of OH production during the electro-Fenton (EF) process, the phenol degradation rate more than doubled and the mineralization yield increased from 78% (final total organic carbon, TOC, concentration of 5.28 mg-C L −1 ) with an uncoated brush to 98.5% (final TOC concentration of 0.34 mg-C L −1 ) with Gr-Brush, following 6 h of EF treatment. Furthermore, the energy required to achieve 40% of phenol mineralization with Gr-Brush was as low as 0.10 kWh g-1 TOC, which outcompeted any other existing graphene-based carbon cathode material coated with either electrochemically-exfoliated graphene (e.g., 0.20 kWh g-1 TOC with carbon cloth) or reduced graphene oxide (rGO) (e.g., 0.53 kWh g-1 TOC with carbon felt), a crucial feature for prospective applications of the novel electrode.